A practical guide to SysML the systems modeling language - Friedenthal, Sanford (Morgan Kaufmann, 2011)
This book is the bestselling, authoritative guide to SysML for systems and software engineers, providing a comprehensive and practical resource for modeling systems with SysML. Fully updated to cover newly released version 1.3, it includes a full description of the modeling language along with a quick reference guide, and shows how an organization or project can transition to model-based systems engineering using SysML, with considerations for processes, methods, tools, and training. Numerous examples help readers understand how SysML can be used in practice, while reference material facilitates studying for the OMG Systems Modeling Professional (OCSMP) Certification Program, designed to test candidates' knowledge of SysML and their ability to use models to represent real-world systems. The authoritative guide for understanding and applying SysML Written by the leader and two key members of the OMG SysML standardization team Language description, examples, and quick reference guide included.
Keywords: Systems engineering.; SysML (Computer science); elektronické knihy; electronic books